The Role of Membrane-Associated E3 Ubiquitin Ligases in Cancer - Chen, Xuankun; Jiang, Li; Zhou, Zhesheng; Yang, Bo; He, Qiaojun; Zhu, Chengliang; Cao, Ji (Frontiers in Pharmacology, 2022)
The cell membrane system comprises the plasma membrane, endoplasmic reticulum, Golgi apparatus, lysosome, mitochondria and nuclear membrane, which are essential for maintaining normal physiological functions of cells. The proteins associated with these membrane-organelles are frequently modified to regulate their functions, the most common of which is ubiquitin modification. So far, many ubiquitin E3 ligases anchored in the membrane system have been identified as critical players facilitating intracellular biofunctions whose dysfunction is highly related to cancer. In this review, we summarized membrane-associated E3 ligases and revealed their relationship with cancer, which is of great significance for discovering novel drug targets of cancer and may open up new avenues for inducing ubiquitination-mediated degradation of cancer-associated membrane proteins via small chemicals such as PROTAC and molecular glue.